Estimating Food Elasticities for Urban and Rural Households in Indonesia - Dian Hafizah; Dedi Budiman Hakim; Harianto Harianto; Rita Nurmalina (Universitas Andalas, 2020)
This study aimed to analyze changes in household consumption patterns in rural and urban areas due to price changes in the rice commodity. The data sources used were the 2016 National Socio-Economic Survey (SUSENAS). Household food consumption data were grouped into ten food groups, while respondent households were grouped into four household groups, i.e., rich urban, poor urban, rich rural, and poor rural groups. The research methodology used was QUAIDS and Elasticity. The results showed that the characteristics of the four household groups on the variable number of household members and the age of the household head had almost the same average. However, the household heads were different in the variable of education length. The longest education was in the rich urban group, while the least was in the poor rural group. Likewise, the highest average income was the rich urban group, and the lowest was the poor rural group. As for commodities, the poor areas share that were greater than the rich ones are rice, other carbohydrates, fat, fruits, spices, and other ingredients. In contrast, the larger commodities in rich areas than in poor areas were meat, eggs-milk-and beans, vegetables, cigarettes, and prepared foods. Of the four commodity groups, the highest share was cigarettes and prepared foods, greater in rich areas than in poor areas, both for urban and rural areas. For the rice commodity, the household group with the highest share was the poor rural group of 0.23, while the smallest was the rich urban group of 0.1033